Gambaran Upaya Mengatasi Kecemasan pada Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisa - Purnami, Ni Wayan; Rahayu, V.M Endang Sri Purwadmi; Dira, I Ketut; Daryaswanti, Putu Intan (Jurnal Kesehatan Medika Udayana, 2019)
ABSTRACT Background: Chronic kidney disease is a progressive and irreversible renal function disorder in which the body's ability to fail to maintain the metabolism and balance of fluids and electrolytes causes uremia. One medicine for the treatment of chronic kidney failure is hemodialysis therapy. Ironically, many patients undergoing hemodialysis experience anxiety. This study aims to determine the efforts to overcome the anxiety of chronic kidney failure in patients undergoing hemodialysis in the Hemodialysis Room of Sanglah Hospital, Denpasar. Method: The research design used was a descriptive analysis approach survey. The study sample used was kidney failure patients who experienced chronic hemodialysis anxiety and light using consecutive sampling technique. Data obtained in April 2012 by filling out a questionnaire about efforts to overcome data analysis anxiety in univariate. Results: Of the 40 respondents who underwent hemodialysis, there were 28 people (70%) experiencing moderate anxiety and 12 people (30%) experiencing mild anxiety. And to overcome anxiety is 27 people (67.50%) doing cognitive therapy and 13 people (32.50) doing relaxation techniques. Conclusions: Some efforts made such as cognitive therapy and relaxation techniques can reduce anxiety in patients with chronic renal failure undergoing hemodialysis.     ABSTRAK Latar belakang: Penyakit ginjal kronis adalah gangguan fungsi ginjal progresif dan irreversible dimana kemapuan tubuh gagal untuk mempertahankan metabolisme dan keseimbangan cairan dan elektrolit sehingga menyebabkan uremia. Salah satu obat untuk pengobatan gagal ginjal kronis adalah dengan cara terapi hemodialisa. Ironisnya, banyak pasien yang menjalani hemodialisa mengalami kecemasan. Penelitian ini bertujuan untuk mengetahui upaya mengatasi kecemasan gagal ginjal kronik asien yang menjalani hemodialisa di Ruang Hemodialisa RSUP Sanglah Denpasar. Metode: Desain penelitian yang digunakan adalah survei pendekatan analisis deskriptif. Sampel penelitian yang digunakan adalah pasien gagal ginjal yang mengalami kecemasan hemodialisa kronis dan cahaya menggunakan teknik consecutive sampling. Data yang didapatkan pada bulan April 2012 dengan cara mengisi kuesioner tentang upaya untuk mengatasi kecemasan analisis data di univariat. Hasil: Dari 40 responden yang menjalani hemodialisa, ada 28 orang (70%) mengalami kecemasan sedang dan 12 orang (30%) mengalami kecemasan ringan. Dan untuk mengatasi kecemasan adalah 27 orang (67,50%) melakukan terapi kognitif dan 13 orang (32,50) melakukan teknik relaksasi. Simpulan: Beberapa upaya yang dilakukan seperti terapi kognitif dan teknik relaksasi dapat menurunkan kecemasan pada pasien gagal ginjal kronik yang menjalani hemodialisis.